Arabic Language Learning Strategies in Increasing Learning Interest in Class VII Mufrodat Material at MTs Al Khairiyah Bandar Lampung - Setiawati, Wiwin; Puspitasari, Reni Dwi (CV. Tripe Konsultan, 2023)
This study aimed to discover the strategies for learning Arabic in increasing students' interest in studying mufrodat material for class VII Mts Al Khiriyah Bandar Lampung. The monotonous strategy causes a lack of students' interest in learning Arabic. This study used descriptive qualitative methods with student research subjects—data collection techniques using questionnaires, interviews and documentation. Interest is one of the student's internal factors significantly influencing learning success. High interest in learning will make students enthusiastic and can easily achieve the competencies to be achieved. To motivate students, certain strategies are needed in learning. This study's results indicate an increase in student learning interest in class VII Mufrodat material at MTs Al Khairiyah Bandar Lampung in terms of the results of interviews and student questionnaires. CTL (Contextual Teaching and Learning) and PAKEM (Participatory, Active, Creative, Effective) use strategies to enhance learning.